A mixed-methods investigation into impact of motivation type on adherence and effect in iCBT for binge eating disorder - T. T. Holmberg; M. Sainte-Marie; E. K. Jensen; E. Runge; J. Linnet; M. B. Lichtenstein; K. Tarp (European Psychiatry, 2023)
Introduction Motivation is an important factor in therapy and potentially even more so in an online setting. Earlier research shows that more autonomously motivated patients have better outcomes and completion rates than more controlled motivated patients´. However, little is known about how motivation type influences treatment effect in an online setting and in patients with binge eating disorder specifically. Objectives This study set out to investigate how motivation type as per the Self-Determination Theory would affect treatment adherence and effect in a sample of 148 patients, undergoing an Internet-based Cognitive Behavioral Therapy (iCBT) for BED. Methods The study was mixed-methods. A sample of 148 patients gave two written qualitative statements regarding their motivation for seeking treatment and reasons for choosing online therapy The statements were transformed into quantitative units via the condensation method. The themes were categorized according to the model by Ryan and Deci based on level of autonomy and perceived locus of causality. This was compared with completion rate and outcomes on eating disorder symptomatology. Completion was designated into three groups. Low adherers - less than six sessions (n=54), high adherers – between 7 and 10 sessions (n =56) and full adherers - 10 session plus follow up (n=37). The effect of the treatment was measured via the Eating Disorder Examination Questionnaire (EDEQ) and Binge Eating Disorder Questionnaire (BEDQ). Results